Tissue-specific landscape of protein aggregation and quality control in an aging vertebrate - Chen, Yiwen R.; Harel, Itamar; Singh, Param Priya; Ziv, Inbal; Moses, Eitan; Goshtchevsky, Uri; Machado, Ben E.; Brunet, Anne; Jarosz, Daniel F. (Developmental cell, 2024)
Protein aggregation is a hallmark of age-related neurodegeneration. Yet, aggregation during normal aging and in tissues other than the brain is poorly understood. Here, we leverage the African turquoise killifish to systematically profile protein aggregates in seven tissues of an aging vertebrate. Age-dependent aggregation is strikingly tissue specific and not simply driven by protein expression differences. Experimental interrogation in killifish and yeast, combined with machine learning, indicates that this specificity is linked to protein-autonomous biophysical features and tissue-selective alterations in protein quality control. Co-aggregation of protein quality control machinery during aging may further reduce proteostasis capacity, exacerbating aggregate burden. A segmental progeria model with accelerated aging in specific tissues exhibits selectively increased aggregation in these same tissues. Intriguingly, many age-related protein aggregates arise in wild-type proteins that, when mutated, drive human diseases. Our data chart a comprehensive landscape of protein aggregation during vertebrate aging and identify strong, tissue-specific associations with dysfunction and disease. [Display omitted] •Tissue-specific protein aggregation is common during vertebrate aging•Biophysical properties and the decline in tissue-specific proteostasis impact these patterns•Aggregation increases in tissues subject to accelerated aging in telomerase mutants•Many proteins that aggregate during physiological aging are linked to disease Chen and Harel use quantitative proteomics to profile protein aggregation in several vertebrate tissues during aging, finding that age-related protein aggregation is highly tissue specific, in part due to tissue-selective defects in protein quality control. Many disease proteins form age-related protein aggregates, potentially contributing to tissue defects during aging.